Identifikasi Waste pada Produksi Kaca Grafir dengan Metode Value Stream Mapping (VSM) di ABC - Maria Prajna Paramitha; Brillian Nur Diansari; Febrina Agusti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The production process of graphite glass at ABC faces challenges in the form of waste that has an impact on low operational efficiency. Waste in production activities can affect the quality, cost, and timeliness of product completion. This study aims to identify the most dominant types of waste and provide relevant improvement recommendations to improve production efficiency. The method used is Value Stream Mapping (VSM), a visual approach that maps the flow of the production process from raw materials to final products. The research stage is carried out through direct observation on the production floor, time study, interviews with employees, and documentation of production activities. The results of the analysis show that the most dominant form of waste is overprocessing, which is a repetitive activity that does not add value to the product. This causes longer production cycle times and reduces the effectiveness of resource use. To overcome this, this study provides several recommendations, including: combining production processes that have similar functions, redesigning workflows to make them more concise, and eliminating activities that do not provide added value. The implementation of this improvement has proven to be effective by increasing the Process Cycle Efficiency (PCE) value from 45% to 67%. The increase in PCE reflects that the production process has become more efficient, the workflow is smoother, and the rate of waste has decreased significantly. In addition, the results of this study also confirm that the application of the VSM method can be a strategic solution in identifying sources of inefficiency, designing continuous improvements, and increasing the competitiveness of companies. Thus, the company is expected to continue to evaluate, control, innovate, and improve technology so that efficiency achievements can be maintained, expanded, and improved consistently and sustainably in the future.